Construction Quality Evaluation Framework of CRTS I Double-Block Ballastless Track Applied in Chinese High-Speed Railway: Based on AHP and Fuzzy Extension Element-Matter Model. Issue 1 (February 2020) - Chen, Huihua; Li, Na; Li, Hujun; Mei, Min; Tang, Rujia
Abstract: The construction quality of CRTS-I double block ballastless track (CRTS-I-DBBT) is the basis of ensuring the comfort, safety and durability of high-speed railway, which helps to promote sustainable development of high-speed railway. This research constructs a quality evaluation framework for CRTS-I-DBBT construction. AHP and Fuzzy Extension Element-matter model were integrated to evaluate the construction quality of CRTS-I-DBBT. Besides, empirical research was carried out to test the applicability of the proposed evaluation system. Besides, the evaluation system will have a wide range of applicability and it will help facilitate the maturation of high-speed railway ballastless track construction quality management.